Development of methodical bases for the construction of organizational components of the business model of a company - A. D. Bobryshev; M. B. Tarabrin; K. M. Tarabrin (Тонкие химические технологии)
Numerous studies of the concept of a business model allow to formulate the most expedient structure of elements and the structure of this new administrative category. At the same time, the majority of researchers casually or intentionally exclude from attention the task of the organization of functioning of a business model.